DEREGULATING THE MALAYSIAN ELECTRICITY MARKET IN THE CONTEXT OF HYBRID POWER SYSTEM - LAI, CARMEN (Universiti Malaysia Sarawak (UNIMAS), 2018)
The ever-increasing demand for electricity has posed a challenge in ensuring secure, reliable energy supply and access to affordable energy. Independent power producers (IPP) were introduced to the generation industry after a major blackout occurred in Peninsular Malaysia during 1992. Since then, the Malaysian Electricity Supply Industry (MESI) has evolved from a monopoly model to the current state where there is competition in the generation sector. The current structure follows the single buyer market model where all generation is procured solely by Tenaga Nasional Berhad (TNB). The single buyer model only introduces a limited form of competition and is not effective in achieving the objective to lower electricity prices. Due to the shortcomings of the single buyer model, this project was carried out to study new strategies towards proposing more competition to be introduced to the electricity supply industry. The current energy market of Malaysia was studied and compared with the international electricity market. Simulations were performed using Matlab software. The data of current electricity market in Malaysia was obtained from available sources to estimate power generation revenue for power producers in a fair and competitive market environment. From the results, the feasibility of deregulating the electricity market was discussed.